Uso del jamboard en exposiciones virtuales con estudiantes de tercero de secundaria en la I.E. Virgen de Loreto, Iquitos 2021 - Pezo Romero, Jesus Antonio (2022)
The objective of the research was to evaluate the use of the Jamboard in virtual exhibitions with third-year high school students at the I.E. Virgin of Loreto - Iquitos. 2021, in this way to validate the usefulness of the digital blackboard and didactic effectiveness, to optimize the way of holding virtual exhibitions with students. The research was experimental and its design was the pre-experimental type: pre-test and post-test design with a single group. The study population consisted of all the third year high school students in the I.E. Virgen de Loreto - Iquitos, enrolled in the year 2021, which were a total of 168 students and an intentional non-probabilistic sampling was used where a single section was chosen, for the application of the Jamboard and there were a total of 35 students. The techniques used to collect the information were the survey and direct observation; and the instruments were the questionnaire and the data collection sheet. For data processing, the computerized statistical package R i386 version 3.6.1 for Windows 7/8/10 was used, with which the data matrix was obtained to organize the data in tables and graphs. For the analysis and explanation of the data, the parametric inferential statistical test t-student (t) was used, where tc = 15.60 was obtained; tt = 6.96; observing that tc> tt accepting the hypothesis: The use of the Jamboard has a positive effect virtual exhibitions with third year high school students in the I.E. Virgin of Loreto - Iquitos. 2021. It was obtained as a result that 100% of students; Before the application of the Jamboard, 62.3% of the students obtained "fair" in their virtual exhibitions, and after the application of the Jamboard, 69.7% of the students obtained "good" in their virtual exhibitions, therefore It can be seen that there is a significant difference between both moments (pre-test and post-test); On the other hand, they gave their opinion on the use of the Jamboard, where a "high" value was obtained with 65.4%.